Effect of Oil Palm Empty Fruit Bunch Biochar and Plant Growth-Promoting Rhizobacteria (PGPR) on the Growth of Maritam (Nephelium ramboutan-ake Leenh.) Seedlings: Pemanfaatan Biochar Tandan Kosong Kelapa Sawit dan Plant Growth-Promoting Rhizobacteria (PGPR) Terhadap Pertumbuhan Bibit Maritam (Nephelium Ramboutan-ake Leenh) - Purwati Purwati; Akhmad Sopian; Raisa Intan Felisa (Agrifarm : Jurnal Ilmu Pertanian, 2026)
This study aimed to analyze and evaluate the effects of oil palm empty fruit bunch (OPEFB) biochar and Plant Growth-Promoting Rhizobacteria (PGPR) on the growth of maritam (Nephelium ramboutan-ake Leenh.) seedlings, as well as to determine whether the OPEFB biochar and maritam seedlings met the Indonesian National Standard (SNI). The experiment was conducted at the Experimental Field of the Faculty of Agriculture, Widya Gama Mahakam University (UWGM), Samarinda, Indonesia. The study employed a Randomized Complete Block Design (RCBD) with a factorial arrangement and three replications. The first factor was the application rate of OPEFB biochar: b₀ = no biochar (control), b₁ = 300 g plant⁻¹, b₂ = 600 g plant⁻¹, and b₃ = 900 g plant⁻¹. The second factor was the PGPR application rate: p₀ = no PGPR (control), p₁ = 100 mL plant⁻¹, p₂ = 200 mL plant⁻¹, and p₃ = 300 mL plant⁻¹. A total of 36 maritam seedlings were used as experimental units. The observed variables included plant height (cm), stem diameter (mm), and number of leaves. The data were analyzed using analysis of variance (ANOVA), followed by a post hoc multiple comparison test to determine significant differences among treatments. The results showed that OPEFB biochar application significantly affected plant height at one month after planting but had no significant effect on stem diameter or number of leaves. Similarly, PGPR application significantly increased plant height at one month after planting but did not significantly affect stem diameter or number of leaves. The interaction between OPEFB biochar and PGPR significantly affected plant height at three months after planting, whereas no significant interaction was observed for stem diameter or number of leaves.